Factors associated with heartworm preventative use in the golden retriever lifetime study - Wisnieski, Lauren; Faulkner, Vina; Faulkner, Charles (Frontiers in Veterinary Science, 2023)
Heartworm disease is preventable with use of heartworm preventatives, but the reported prevalence of heartworm preventative use is low, some estimates falling around 50% of dogs. However, there are very few estimates of prevalence and its associated factors. Therefore, we aimed to estimate prevalence and evaluate factors, including vaccination status, demographics, lifestyle, physical conditions, medications and supplements, and environment and living conditions, for their association with heartworm preventative use in a large dataset from the Golden Retriever Lifetime Study (N = 2998). In our sample, the prevalence of heartworm use was 39.5%. Due to the large number of predictors evaluated, we built a bootstrapped elastic net logistic regression model, which is robust to overfitting and multicollinearity. Variables were evaluated by calculating covariate stability (>80%) and statistical significance (P<0.02). In our elastic net model, receiving vaccinations (rabies, Bordetella, or any other vaccine), being located in the Southern U.S., being altered, being in the top quartile of height, having an infectious disease or ear/nose/throat system disease diagnosis, being on heartworm preventatives in the past, currently being on tick preventative, having sun exposure in an area with concrete flooring, living in a house with more rooms with carpeted floors, and spending time on hardwood flooring inside were associated with greater odds of heartworm preventative use. Supplementation use and being intact were associated with lower odds of heartworm preventative use. Although the model had poor predictive ability (area under the receiver operator characteristic curve = 0.50), the explanatory factors we identified can be used to improve client communication. In addition, target populations for educational interventions and outreach can be identified. Future studies can validate the findings in a more diverse population of dogs.